The role of the gut microbiota in the pathogenesis and treatment of Alzheimer disease – review - Wojtuś, Magda; Tomaszuk, Sebastian; Wąsik, Karolina (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Currently, the role of the gut microbiota in the pathogenesis of different diseases is being widely researched, the understanding of whether the dysbiosis of the gut flora demonstrates the significant role in Alzheimer disease (AD) is accentuated. The aim of this paper is to summarize the existing paper about the role of the gut microbiota - its diversity, stability and composition in this condition. The search was conducted using PubMed and Google Scholarship databases. Brief description of the state of knowledge: It is still uncertain if alteration in gut microbiome is a consequence of AD or its risk factor, but some findings suggest that the intestinal flora is able to influence the activity of the brain and lead to its dysfunctions. There is also the association between composition of the gut microbiome and AD. Results indicate that affected patients had less heterogeneity in their microbiome and the progression of AD led to alterations in the bacterial flora. Introducing modifications of the gut microbiota is considered as a therapeutic option for AD. Following personalized diet, probiotics, prebiotics and synbiotics administration or fecal microbiota transplantation (FMT) may be beneficial for affected patients. Conclusions: The subject of the role of the gut microbiota merits further research as foregoing results of conducted studies are pointing to its possibly meaningful role. Presently, still more data is needed as most of the research was collected on animal models and the analysis conducted on humans remains insufficient. We conclude that further studies are warranted in order to fully understand the pathophysiology of the disease and the possible usefulness of microbiome therapy.